2016
DOI: 10.1038/srep36290
|View full text |Cite
|
Sign up to set email alerts
|

MTHFR c.677C>T Inhibits Cell Proliferation and Decreases Prostate Cancer Susceptibility in the Han Chinese Population in Shanghai

Abstract: Methylenetetrahydrofolate reductase (MTHFR) c.677C>T and c.1298A>C variants were known to be associated with prostate cancer (PCa) risk with conflicting results, because of MTHFR and nutrient status interaction in the prostate development. In this large-scale, hospital-based, case-control study of 1817 PCa cases and 2026 cancer-free controls, we aimed to clarify the association between these two MTHFR variants and PCa risk in Shanghai and to explore the underlying molecular mechanisms. We found that both the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Furthermore, the sample sizes were relatively small in most of included studies. A functional study indicated that MTHFR rs1801133 G>A polymorphism was a protective factor of prostate cancer (PC) susceptibility by elevating homocysteine level, promoting cell apoptosis, and inhibiting proliferation of PC cells [ 21 ]. In the present study, we found that MTHFR rs1801133 A allele might be a protective factor for NSCLC, which was similar to the findings of previous study conducted in Eastern Chinese Han populations.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the sample sizes were relatively small in most of included studies. A functional study indicated that MTHFR rs1801133 G>A polymorphism was a protective factor of prostate cancer (PC) susceptibility by elevating homocysteine level, promoting cell apoptosis, and inhibiting proliferation of PC cells [ 21 ]. In the present study, we found that MTHFR rs1801133 A allele might be a protective factor for NSCLC, which was similar to the findings of previous study conducted in Eastern Chinese Han populations.…”
Section: Discussionmentioning
confidence: 99%
“…In cells with DNA damage, negatively charged DNA fragments are released from the nucleus and migrate towards the anode. 16 The restoration of miR-375 resulted in a significant increase in DNA damage compared to that inducted by the scrambled control or miR-NC ( Figure 4C and Ds). Interestingly, we also observed that scratch closure and cell proliferation were significantly inhibited in MG63 cells transfected with miR-375-mimics ( Figure 4A, B and E).…”
Section: Mir-375 Modulates Cis-induced Dna Damage In Mg63 Cells and Amentioning
confidence: 87%
“…A number of studies were conducted to check the association of MTHFR C677T gene polymorphism with the prostate cancer [35-47]. Very few studies were published, which evaluated MTRR A66G polymorphism as risk for prostate cancer [39,40,48-50].…”
Section: Introductionmentioning
confidence: 99%